2018
DOI: 10.1016/j.celrep.2018.08.094
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell Activation Leads to Constitutive Formation of Liver Tissue-Resident Memory T Cells that Seed a Large and Flexible Niche in the Liver

Abstract: Graphical Abstract Highlights d TCR stimulation is essential for liver Trm cell formation d Liver Trm cells require IL-15 d Local antigen presentation and inflammation enhance liver Trm cell formation d Newly formed liver Trm cells do not displace existing Trm cell populations SUMMARY Liver tissue-resident memory T (Trm) cells migrate throughout the sinusoids and are capable of protecting against malaria sporozoite challenge. To gain an understanding of liver Trm cell development, we examined various condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 58 publications
(48 reference statements)
2
85
0
Order By: Relevance
“…In lymphoid sites, such as lymph nodes, tissue memory T cells exhibit increased expression of transcription factors and functional markers associated with stemness and denoting maintenance in a more quiescent state compared with memory T cells in spleen and bone marrow, which exhibit a more differentiated state with increased turnover ( Miron et al., 2018 ). Conversely, T RM localized across the GI tract exhibit distinct phenotypes and metabolic signatures whether they localize to the small intestine, associated lymphoid tissue, or the pancreas ( Weisberg et al., 2019 ), and unique localization of T RM in liver sinusoids requires specific adaptations ( Holz et al., 2018 ; McNamara et al., 2017 ). Further elucidation of tissue memory T cell heterogeneity and tissue adaptations will be facilitated by applying scRNA-seq technologies.…”
Section: Immunity In Space and Timementioning
confidence: 99%
“…In lymphoid sites, such as lymph nodes, tissue memory T cells exhibit increased expression of transcription factors and functional markers associated with stemness and denoting maintenance in a more quiescent state compared with memory T cells in spleen and bone marrow, which exhibit a more differentiated state with increased turnover ( Miron et al., 2018 ). Conversely, T RM localized across the GI tract exhibit distinct phenotypes and metabolic signatures whether they localize to the small intestine, associated lymphoid tissue, or the pancreas ( Weisberg et al., 2019 ), and unique localization of T RM in liver sinusoids requires specific adaptations ( Holz et al., 2018 ; McNamara et al., 2017 ). Further elucidation of tissue memory T cell heterogeneity and tissue adaptations will be facilitated by applying scRNA-seq technologies.…”
Section: Immunity In Space and Timementioning
confidence: 99%
“…Several studies have shown that local antigen encounter or deposition usually perpetuates the establishment of high numbers of CD8 ϩ T RM cells in various anatomical sites, including the liver (12,(52)(53)(54). Studies in mice and humans suggest that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…DNA immunization occurs in the draining cervical lymph nodes (28,35) and likely does not facilitate local antigen encounter/deposition in the liver to establish high numbers of intrahepatic CD8 ϩ T RM cells. A caveat with this interpretation is that a recent study that analyzed adoptively transferred CD8 ϩ T cells showed that the lodgment of CD8 ϩ T RM cells in the liver is both activation and interleukin-15 (IL-15) dependent, and inflammatory signals (e.g., type I interferon inducers) can enhance the number of intrahepatic CD8 ϩ T RM cells (54). Thus, in addition to facilitating local antigen encounter, rAAV-NS5B vaccination could induce higher levels of IL-15 and relevant inflammatory signals compared to pVAX-NS5B-PRF vaccination in order to increase the numbers of intrahepatic CD8 ϩ T RM cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To put this into perspective, liver T RM cells induced by an RAS vaccine in a similar model only had an estimated halflife of 28 days and with multiple dosing required to achieve a significant level of protection. 5,10 The new vaccine candidate developed by Holz et al represents an important advance in global efforts toward developing a malaria vaccine. However, some caveats will need to be addressed, including several translational challenges.…”
mentioning
confidence: 99%